Report of a rare fistula between a Studer neobladder and external iliac artery - Kuntz, Nicholas J; Inman, Brant A (Canadian Urological Association Journal, 2013)
A neobladder-arterial fistula is a very rare complication following cystectomy, with only 1 previously reported case. Delay in diagnosis can be rapidly fatal and requires prompt intervention. We report the case of a 63-year-old male who developed massive hematuria, and was found to have a fistula between the right external iliac artery and Studer neobladder during emergent exploratory laparotomy. Treatment success relies on a high index of suspicion and may include open operative intervention.